1.
-2 + 8
Explanation
The given expression is -2 + 8. When we add -2 and 8 together, we get 6. Therefore, the answer to the expression is 6.
2.
5 - 14
Explanation
The given expression is 5 - 14, which equals -9.
3.
(-4)(-12)
Explanation
The given expression (-4)(-12) can be simplified by multiplying the two negative numbers. When two negative numbers are multiplied, the result is always positive. Therefore, (-4)(-12) equals 48.
4.
60/-12
5.
-23 + (-5)
Explanation
The given expression is the sum of -23 and -5. When adding two negative numbers, the result is always negative. Therefore, the correct answer is -28.
6.
-7 - 15
Explanation
The correct answer is -22 because when we subtract -15 from -7, we add the opposite of -15 which is 15. So, -7 + 15 equals 8. Therefore, -7 - 15 is equal to -22.
7.
(-5)(10)
Explanation
The given expression is the product of -5 and 10. When we multiply a negative number by a positive number, the result is always negative. Therefore, the product of -5 and 10 is -50.
8.
-100/10
Explanation
The given expression is -100 divided by 10. When we divide -100 by 10, we get -10 as the result. This is because when a negative number is divided by a positive number, the quotient is negative. Therefore, -100 divided by 10 equals -10.
9.
-4 + 9 - (-12)
Explanation
The given expression is -4 + 9 - (-12). To simplify this expression, we can remove the parentheses by changing the sign of the term inside the parentheses. So, -4 + 9 + 12 equals 17. Therefore, the answer is 17.
10.
(-3)(6)(-10)
Explanation
The given expression (-3)(6)(-10) can be simplified by multiplying the numbers together. When we multiply -3, 6, and -10, we get -180. However, since the question asks for the absolute value, we take the positive value of -180, which is 180. Therefore, the correct answer is 180.
11.
(-6)(7) - 8
Explanation
The given expression is (-6)(7) - 8. To simplify this expression, we first multiply -6 and 7, which gives us -42. Then we subtract 8 from -42, resulting in -50. Therefore, the correct answer is -50.
12.
Evaluate when x = 2 and y = -5
2x + y
Explanation
The given expression is 2x + y. Substituting the values x = 2 and y = -5 into the expression, we get 2(2) + (-5) = 4 - 5 = -1. Therefore, the answer is -1.
13.
Evaluate when x = 2 and y = -5
xy - 4
Explanation
When x = 2 and y = -5, we can substitute these values into the expression xy - 4. Therefore, we have (2)(-5) - 4 = -10 - 4 = -14. Hence, the answer is -14.
14.
Evaluate when x = 2 and y = -5
3y - 2x
Explanation
To evaluate the expression 3y - 2x when x = 2 and y = -5, we substitute the given values into the expression. Therefore, we have 3(-5) - 2(2). Simplifying this expression, we get -15 - 4, which equals -19. So, the answer is -19.
15.
Find
16.
Find
17.
Solve.
One solution is y = 7. What is the other solution?
Remember to answer with the variable. Ex: y = 10
Explanation
The other solution to the equation is y = -7.
18.
Solve.
-x = 8
Remember to answer with the variable. Ex: x = 10
Explanation
The equation -x = 8 can be solved by multiplying both sides of the equation by -1. This will give us x = -8, which means that the value of x that satisfies the equation is -8.